(untitled) (Research, Society and Development, 2021)
Teacher training in higher education in health is responsibility of graduate studies, and the teaching internship (TI) appears as an opportunity to meet this purpose. This study aimed to recognize the limits and potential of TI in teachers training for higher education in health. This is an integrative literature review which included eight articles published from 2015 on. Thematic content analysis was carried out, based on the following categories: weaknesses, challenges, strengths, opportunities in TI. It was found, as weaknesses, that the TI is presented as a place of practice, of practical concerns and purpose deviations, producing ideas of teaching as a simple activity. The challenges identified were: research centrality in graduate studies, teaching process centered on technical content transmission, incipient pedagogical training and oriented towards SUS, limited teacher training, lack of definition on roles and teacher profile, irrelevance in the postgraduate assessment system. The indicated strengths were: TI as a place of experience, interpersonal relationships, operative appropriation of teaching, trainee’s contributions. As opportunities, the following were observed: TI as a place of learning, critical reflection on practice, teacher training as a process, expanded teacher training, teaching-research-extension articulation, normative flexibility. It is concluded that teaching demands prioritization in graduate studies, and that producing new and robust knowledge about TI will contribute for training committed teachers on consolidating and strengthening SUS through the qualification of higher education in health.